Age distribution of wrestlers participating in the World Championships - Latyshev, M.; Shandrygos, V.; Tropin, Y.; Polianychko, O.; Deineko, A.; Lakhtadyr, O.; Mozoliuk, O. (Acta Kinesiologica, 2021)
The age of peak competitive performance is particularly important as the entire sports career in each sport is planned on its basis. Depending on the sport and gender of the athlete, the age of peak competitive performance varies considerably.The objective of the study -to determine the age indicators of the wrestlers who participated in the World Championships, depending on the place taken and the weight group. We have studied 332 sports careers ofthe freestyle and Greko-Roman male wrestlers from 1stto 8thranks who participated in the World Championships 2017, 2018 and 2019. The following indicators are analyzed: the average age, the average age of the international career start, the average age of first success and the proportion of athletes who achieved success at junior level. Results.The average age of the wrestlers is 26.5 ± 3.6 years: the medalists are slightly younger -26.3 ± 3.4 years, and non-medalists are older than 26.7 ± 3.8 years. The analysis of the distribution of the age of peak competitive performance of athletes-medalists has shown the following results: there are 67.7 % of medalist among the athletes who are 22-28 years old, 11.8% among those who are younger than 23 years old and only 26.6% among those who are older than 28 years. More than half (53.4%) of medalists achieved success being juniors, while for non-medalists this proportion is only 38.2%. The linear regression coefficient between the age and the weight of athletes is positive and is equal to 0.47 kg per year. The results obtained on the medalists show that the period for achieving the peak competitive performance is limited and quite a few athletes can succeed beyond a certain period of age.